The ISO 1400 challenge - Campbell, Catherine; Nicholas and Smith Pty Ltd. (Australia : Nicholas and Smith Nicholas and Smith Pty Ltd.)
Provides a practical guide to key principles involved in environmental management. Three case study companies, a food manufacturer, mining contractor and a local council show how they implemented and used an environmental management system to improve their operations.
Keywords: ISO 14000 Series Standards